Comparison of the Diagnostic Efficacy of Ultrasound‐Guided Core Needle Biopsy With 18‐ Versus 20‐Gauge Needles for Thyroid Nodules. (25th March 2018) - Ahn, Hye Shin; Seo, Mirinae; Ha, Su Min; Kim, Hee Sung
Abstract : Objectives: To compare the diagnostic efficacy, complication rate, and core needle biopsy (CNB) specimen yield in 18‐ versus 20‐gauge ultrasound (US)‐guided CNB for diagnosis of thyroid nodules. Methods: We included 81 consecutive thyroid nodules with US‐guided biopsy by a 20‐gauge core needle and 86 consecutive thyroid nodules with US‐guided biopsy by an 18‐gauge core needle during 2 years. The rate of inconclusive results, including nondiagnostic or atypia/follicular lesion of undetermined significance, was compared. The diagnostic performance for malignancy was assessed in nodules with a final diagnosis. The complication rate and CNB specimen yield were also compared. Results: Eighteen‐gauge CNB showed a lower rate of nondiagnostic results (1.2% versus 8.6%; P  = .024) than 20‐gauge CNB; however, the rates of atypia/follicular lesion of undetermined significance and inconclusive results were not significantly different between the groups ( P  > .05). In addition, 18‐gauge CNB showed higher sensitivity (75.0% versus 66.7%), a higher negative predictive value (83.9% versus 75.9%), and higher accuracy (78.3% versus 74.4%) for detecting malignancy than 20‐gauge CNB, although the results did not achieve statistical significance. No major complications occurred in either of the CNB groups. The 18‐gauge needle group had significantly fewer CNBs and larger specimen diameters ( P  < .001). Conclusions: Core needle biopsy with an 18‐gauge needle could be more effective for the diagnosis of thyroid nodules than CNB with a 20‐gauge needle.